School reopening: Evidence-based recommendations during COVID-19 pandemic in Indonesia - Raden Yuli Kristiyanto; Lily Chandra; Hermawan Hanjaya; Mohamad Saifuddin Hakim; Dian Kesumapramudya Nurputra (Journal of Community Empowerment for Health, 2020)
Since the first Coronavirus Disease 2019 (COVID-19) case was reported, it has run amok and caused global changes. It has affected human lives in almost every aspect, including education. In response to COVID-19, governments and policy-makers decided to shift the educational activities into online learning and institute school closure. As of March 2020, many countries worldwide have implemented school closure, including Indonesia. Large scale social distancing and stay-at-home policies have begun to negatively impact society’s physical and mental health. As people start to adapt to the first wave of the COVID-19 pandemic, policy-makers and the government need to consider how to reopen the schools and its system to keep students and staff safe. School reopening is an important step toward loosening the lockdown. Schools play a crucial role in preserving children's well-being. The objective of this review was to give a recommendation to facilitate school reopening. Research articles were gathered and assessed based on the themes of the articles. Forty articles were found reflecting SARS-CoV-2 and school reopening. Findings were adapted and modified according to Indonesian situations during the SARS-CoV-2 pandemic. Indonesia is currently preparing the first steps toward school reopening. For schools to be reopened, there are several health measurements that need to be considered. A good collaboration between various authorities and stakeholders is essential in school reopening so that children’s safety and disease mitigation strategies remain stable. This review presents insights and recommendations for every element involved in school safety including the government, schools, teachers, parents and students including what each needs to do to prepare in advance for the up-coming decision to reopen schools.